Truncated-semaphorin3A is a potential regulatory molecule to restore immune homeostasis in immune-mediated diseases - Eiza, Nasren; Kessler, Ofra; Sabag, Adi; Neufeld, Gera; Jones, E. Yvonne; Vadasz, Zahava (Frontiers in Pharmacology, 2023)
Regulatory molecules have recently been recognized for their beneficial effects in the treatment of immune-mediated diseases, rather than using cytotoxic immune-suppressing drugs, which are associated with many unwanted side effects. Semaphorin3A (sema3A), a unique regulatory master of the immune system, was shown to be decreased in the serum of systemic lupus erythematosus (SLE) patients, in association with disease severity. Later, we were able to show its extremely beneficial effect in treating lupus nephritis in the NZB/W mice model. The mechanisms by which sema3A maintains its regulatory effect is by binding the regulatory receptor CD72 on B cells, thereby reducing the threshold of BCR signaling on B cells and reducing the production of pro-inflammatory cytokines. The aim of this study was to generate a stable sema3A molecule, easy to produce with a higher binding capacity to CD72 receptor rather than to Neuropilin-1 (NRP-1) receptor, which is expressed in many cell types. Using the crystallographic structure of parental sema3A, we synthesized a new secreted (shorter) sema3A derivative, which we called truncated sema3A (T-sema3A). The new molecule lacked the NRP-1 binding domain (the C-terminal site) and has an artificial dimerization site at position 257 (serine residue was exchanged with a cysteine residue). To facilitate the purification of this molecule we added Histidine epitope tag in frame upstream to a stop codon. This construct was transfected using a viral vector to 293HEK cells to generate cells stably expressing T-sema3A. T-sema3A is shown to be with a higher binding ability to CD72 than to NRP-1 as demonstrated by a homemade ELISA. In addition, T-sema3A was shown to be a regulatory agent which can induce the expression of IL-10 and TGF-β and reduce the secretion of pro-inflammatory cytokines such as IL-6, IFN-γ, and IL-17A from human T and B-lymphocytes. Keeping this in mind, T-sema3A is highly effective in maintaining immune homeostasis, therefore, becoming a potential agent in restoring the regulatory status of the immune system in immune-mediated diseases.